Prediagnostic consumption of vitamin D, calcium and dairy products and colorectal cancer survival: results from the Newfoundland Colorectal Cancer Registry Cohort Study. Issue 2 (28th July 2022) - Zhu, Yun; Zhao, Jing; Vallis, Jillian; Shi, Fuyan; Woodrow, Jennifer R.; Kong, Yujia; Zhai, Guangju; Parfrey, Patrick; Mclaughlin, John R.; Wang, Peizhong Peter
Abstract: Vitamin D, Ca and dairy products are negatively associated with colorectal cancer (CRC) incidence, but little is known of their influence on CRC survival. To investigate prediagnostic intakes of vitamin D, Ca and dairy products for their relevance to CRC prognosis, we analysed 504 CRC patients enrolled in the Newfoundland Colorectal Cancer Registry Cohort Study who were diagnosed for the first time with CRC between 1999 and 2003. Follow-up for mortality and cancer recurrence was through April 2010. Data on diet and lifestyle factors were gathered via a validated, semi-quantitative FFQ and a Personal History Questionnaire. Multivariate Cox models estimated hazard ratios (HR) and 95 % CI for the relationship of prediagnostic intakes of vitamin D, Ca and dairy products with all-cause mortality (overall survival, OS) and disease-free survival (DFS) among CRC patients. We found that prediagnostic Ca intake from foods, but not total Ca intake, was negatively associated with all-cause mortality (HR for Q2 v . Q1, 0·44; 95 % CI, 0·26, 0·75). An inverse relationship was also seen in a dose–response fashion for prediagnostic cheese intake (HR for Q4 v . Q1, 0·57, 95 % CI, 0·34, 0·95, P trend = 0·029). No evidence for modification by sex, physical activity, alcohol drinking and cigarette smoking was observed. In summary, high prediagnostic intakes of cheese and Ca from foods may be associated with increased survival among CRC patients. By manipulating diet, this study may contribute to the development of novel therapies that add to the armamentarium against CRC. Replication studies are required before any nutritional interventions are made available.